REV-ERB-alpha and -beta coordinately regulate astrocyte reactivity and proteostatic function - Collin J. Nadarajah; Michelle Y. Li; Elsa I. Quillin; Kevin Boyer; Julie M. Dimitry; Yining Chen; Melvin W. King; Ibrahim O. Saliu; Jiyeon Lee; Patrick W. Sheehan; Albert A. Davis; Mitchell A. Lazar; et al. (Proceedings of the National Academy of Sciences, 2026)
The molecular circadian clock is a ubiquitous transcriptional–translational feedback loop that regulates CNS function, glial responses, and neurodegenerative pathology. The nuclear receptors REV-ERB-α ( Nr1d1 ) and REV-ERB-β ( Nr1d2 ) are components of the core circadian clock which regulate metabolism, neuroinflammatory responses, synaptic pruning, and protein aggregation, though the cell type–specific effects and relative compensatory effects of REV-ERB-α AND -β in the brain are unknown. To study the CNS functions of REV-ERBs, we developed mouse lines with global or astrocyte-specific, conditional knockout of both REV-ERB-α and -β. We demonstrate that inducible postnatal global deletion of both REV-ERB-α and -β unmasks extensive transcriptional changes in the brain in disease-relevant pathways such as protein catabolism, complement, and oxidative stress which are not observed with REV-ERB-α deletion alone, and drives spontaneous astrocyte reactivity. Astrocyte-specific deletion of REV-ERB-α/-β recapitulates this spontaneous astrocyte reactivity phenotype, indicating that REV-ERBs regulate astrocyte activation in a cell-autonomous manner downstream of the core circadian clock. Upstream transcription factor analysis revealed that REV-ERB-α/-β repress transcription of Stat3 , and astrocytic deletion of REV-ERBs induced astrocytic STAT3 expression and downstream STAT3-mediated gene expression, providing a mechanistic link to the astrocyte reactivity shift. Dual REV-ERB deletion enhanced astrocyte alpha-synuclein uptake and protein degradation in vitro and mitigated alpha-synuclein spreading pathology in an in vivo model of Parkinson’s Disease. This study reveals REV-ERBs as regulators of astrocyte function and implicates astrocyte REV-ERBs as potential therapeutic targets to prevent synucleinopathies and other neurodegenerative pathologies.